2017
DOI: 10.1175/jas-d-16-0222.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boundary Layer Roll Vortices on the Development of an Axisymmetric Tropical Cyclone

Abstract: In this study, the authors numerically investigate the response of an axisymmetric tropical cyclone (TC) vortex to the vertical fluxes of momentum, heat, and moisture induced by roll vortices (rolls) in the boundary layer. To represent the vertical fluxes induced by rolls, a two-dimensional high-resolution Single-Grid Roll-Resolving Model (SRM) is embedded at multiple horizontal grid points in the mesoscale COAMPS for Tropical Cyclones (COAMPS-TC) model domain. Idealized experiments are conducted with the SRM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…There is a rapid speed jump of ∼45 m⋅s −1 at 500 m. Moreover, the 10-m wind speed increases suddenly from ∼30 m⋅s −1 in the updraft to ∼60 m⋅s −1 in the downdraft, suggesting the influence of the small-scale feature on the near-surface wind gusts. While the strong wind gusts result from vertical momentum transport ( 21 25 ), the superposition of the perturbation flow of the cyclonic circulation can further enhance the wind gusts on the radially outward side.…”
Section: Simulated Tornado-scale Vortexmentioning
confidence: 99%
“…There is a rapid speed jump of ∼45 m⋅s −1 at 500 m. Moreover, the 10-m wind speed increases suddenly from ∼30 m⋅s −1 in the updraft to ∼60 m⋅s −1 in the downdraft, suggesting the influence of the small-scale feature on the near-surface wind gusts. While the strong wind gusts result from vertical momentum transport ( 21 25 ), the superposition of the perturbation flow of the cyclonic circulation can further enhance the wind gusts on the radially outward side.…”
Section: Simulated Tornado-scale Vortexmentioning
confidence: 99%
“…The latter are believed to result from small-scale coherent structures in the TC boundary layer (Wurman and Winslow, 1998;Morrison et al, 2005;Lorsolo et al, 2008;Kosiba et al, 2013;Kosiba and Wurman, 2014). The small-scale coherent structures may have significant implications for the vertical transport of energy in TCs and thus TC intensity and structure (Zhu, 2008;Rotunno et al, 2009;Zhu et al, 2013;Zhang, 2014, 2015;Gao et al, 2017). While understanding of the coherent structure is very important for mitigating TC damage and understanding of TC intensity and structure changes, for now direct in situ observation and remote-sensing measurements can only provide very limited information.…”
Section: Introductionmentioning
confidence: 99%
“…In the TC boundary layer (TCBL), observational analyses suggest that horizontal streamwise roll vortices prevail with sub-kilometer to multi-kilometer wavelengths (Wurman and Winslow, 1998;Katsaros et al, 2002;Morrison et al, 2005;Lorsolo et al, 2008;Ellis and Businger, 2010;Foster, 2013). Studies found that the rolls can result from the inflection point instability of the horizontal wind profiles in the TCBL (Foster, 2005;Gao and Ginis, 2014) and have sig-nificant influences on the vertical transport of energy in TCs (Zhu, 2008;Rotunno et al, 2009;Zhu et al, 2013;Zhang, 2014, 2015;Gao et al, 2017). The TCBL is known to play a critical role in transporting energy and controlling TC intensity (Braun and Tao, 2000;Rotunno et al, 2009;Smith and Montgomery, 2010;Bryan, 2012;Zhu et al, 2013;Green and Zhang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Svensson et al (2017) presented results concerning roll persistence during situations with advection to a strongly stratified boundary layer via SAR and aircraft data. Gao et al (2017) studied the impact of rolls on the intensification process of the TC's and identified a pathway by which rolls can affect the structure and the intensification of the simulated TC's. SAR can be utilized in observing MABL rolls in day-night conditions, resulting from the high resolution (<100 m) and capability of penetrating clouds (Katsaros et al, 2000(Katsaros et al, , 2002Li et al, 2013aLi et al, , 2013bReppucci et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%